EDUKASI PENTINGNYA NUTRISI IKAN UNTUK MENCEGAH STUNTING DI PONDOK PERASI, KECAMATAN AMPENAN, MATARAM - Wastu Ayu Diamahesa; Thoy Batun Citra Rahmadani; Septiana Dwiyanti; Yuliana Asri; Nuri Muahiddah; Rangga Idris Affandi; Sahrul Alim; Muhammad Sumsanto; Bagus Dwi Hari Setyono; Dewi Putri Lestari; Salnida Yuniarti Lumbessy; Nanda Diniarti; Andre Rachmat Scabra; Damai Diniariwisan (Universitas Mataram, 2023)
Stunting is a health issue that impacts children on a local, national, and international scale. High rates of early marriage are directly associated to the prevalence of stunting in Indonesia. Children in early childhood who marry and become pregnant without the knowledge, mental and financial readiness to become good mothers pose a grave threat to the quality of the future human resources. The problem of stunting is influenced not only by a single element, but also by multiple factors, the most significant of which is the fulfillment of nutrient needs, particularly protein, in this case through fish consumption. This community service project aims to provide counseling or instruction on the significance of fish nutrition in preventing stunting, as well as teach participants how to make cookies from wet anchovies. This method of community service is counseling, which consists of multiple stages, including preparation, distribution of materials, pre- and post-testing, explanation of method to make anchovy cookies, and tasting fish-based processed foods together. From the findings of the pretest given by the speaker to the respondents, 50% of the respondents consumed around 200 g of fish on the day of counseling, and 100% of the respondents were motivated to consume fish following the counseling. In addition to emphasizing the significance of consuming fish on a regular basis for proper nutrition, the presenters demonstrated how to make anchovy cookies as an alternative snack for children. The outcome of this service activity is that the respondents are enthusiastic and inspired by the knowledge offered by the presenters, and are interested in preparing anchovy-based cookies at home.